2018
DOI: 10.1021/acs.jpca.7b09450
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Elementary Reaction Steps in Thermal Decomposition Processes of Syringol-Type Monolignol Compounds

Abstract: This paper theoretically investigated a large number of reaction pathways and kinetics to describe the vapor-phase pyrolytic behavior of several syringol-type monolignol compounds that are derived from the primary pyrolysis of lignin: 1-(4-hydroxy-3,5-dimethoxyphenyl)prop-2-en-1-one (HDPP), sinapyl alcohol, 3-hydroxy-1-(4-hydroxy-3,5-dimethoxyphenyl)propan-1-one (HHDPP), 1-(4-hydroxy-3,5-dimethoxyphenyl)propane-1,3-diol (HDPPD), and syringol. The possible pyrolytic pathways involving unimolecular decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Furutani et al 32 theoretically investigated the pyrolysis behaviour of phenol-type monolignol compounds released from the primary heterogeneous pyrolysis of lignin. They observed that all these phenol compounds convert to phenol by sidechain cleavage at high temperatures, whereas the dominant channel below 1000 K produces cyclopentadiene species.…”
Section: General Structure Of the Kinetic Modelmentioning
confidence: 99%
“…Furutani et al 32 theoretically investigated the pyrolysis behaviour of phenol-type monolignol compounds released from the primary heterogeneous pyrolysis of lignin. They observed that all these phenol compounds convert to phenol by sidechain cleavage at high temperatures, whereas the dominant channel below 1000 K produces cyclopentadiene species.…”
Section: General Structure Of the Kinetic Modelmentioning
confidence: 99%
“…These studies provide information on the dominant types of reactions involved such as concerted, free-radical, or ion-driven mechanisms. In addition, mechanistic studies describe the type of reaction intermediates and competing pathways involved in the product formation (Asatryan, Bennadji, Bozzelli, Ruckenstein, & Khachatryan, 2017;Bahrle, Custodis, Jeschke, van Bokhoven, & Vogel, 2014;Custodis et al, 2014;Furutani, Dohara, Kudo, Hayashi, & Norinaga, 2018;Khachatryan et al, 2016;Kibet, Khachatryan, & Dellinger, 2012;Kim, Bai, Cady, Gable, & Brown, 2015;Koirala, Villano, Carstensen, & Dean, 2013;Qi, Zhang, Kudo, Norinaga, & Hayashi, 2017;Seshadri & Westmoreland, 2012;Shen, Jarboe, et al, 2015;Wornat, Ledesma, & Marsh, 2001;Xu, Khachatryan, Baev, & Asatryan, 2016). Advances in analytical techniques have made it possible to even detect intermediate radicals and important product species (Bahng et al, 2009;Kanaujia, Sharma, Agrawal, & Garg, 2013;Michailof, Kalogiannis, Sfetsas, Patiaka, & Lappas, 2016;Negahdar et al, 2016;Pouwels, Eijkel, & Boon, 1989;Sarrut et al, 2015;Traore, Kaal, & Martinez Cortizas, 2016).…”
mentioning
confidence: 99%
“…Therefore, the elementary reaction rate constant of monolignol gas-phase decomposition was estimated on the basis of the quantum chemistry calculations and transition-state theory. Detailed chemical reaction models were also constructed for the pyrolysis process of resorcinol, catechol, guaiacol, syringol-based monolignol, and phenol-based monolignol …”
Section: Detailed Chemical Kinetic Modeling Of Primary Reactionsmentioning
confidence: 99%
“…Therefore, the elementary reaction rate constant of monolignol gas-phase decomposition was estimated on the basis of the quantum chemistry calculations and transitionstate theory. Detailed chemical reaction models were also constructed for the pyrolysis process of resorcinol, 40 catechol, 41 guaiacol, syringol-based monolignol, 42 and phenol-based monolignol. 43 Therefore, a reliable prediction method for the thermochemical reaction of solid fuels that minimizes the amount of empirical information should be established in the future.…”
Section: Detailed Chemical Kinetic Modeling Ofmentioning
confidence: 99%